Influence of Polypropylene Fiber on Mechanical and Shrinkage Behavior of Porcelain Based Geopolymer - Klingsad , Rada; Israngkura Na Ayudhya, Borvorn (Civil Engineering Journal, 2025)
This study examines the effects of polypropylene (PP) fiber content and initial curing temperature on shrinkages, mechanical properties, and microstructural characteristics of porcelain-based geopolymers. Geopolymer mixes were prepared with PP fiber dosages of 0.5%, 1.0%, 1.5%, and 2.0% by weight and initially cured at 60 °C, 75 °C, 90 °C, and 105 °C. Autogenous and drying shrinkage were monitored at 24 h, 72 h and 3, 7, 14, 21, 28, 60, 90, and 120 days, while compressive and splitting tensile strengths were tested at 3, 7, 14, 21, and 28 days. The results demonstrated that the incorporation of PP fiber not only shortened the setting time but also significantly reduced both autogenous and drying shrinkage of the geopolymer mortar. The most favorable performance was observed in specimens containing 2.0% PP fiber cured at 105 °C, which exhibited the lowest shrinkage values. Autogenous shrinkage was 439 μɛ at 24 h and 392 μɛ at 120 days, while drying shrinkage was 544 μɛ at 24 h and 194 μɛ at 120 days. Increasing fiber content decreased porosity, producing a more compact, homogeneous matrix and improving mechanical performance of concrete specimens, particularly splitting tensile strength; the optimal dosage was 2%, yielding 28‑day compressive strength of 41.03 N/mm² and splitting tensile strength of 7.65 N/mm².